METODE PENANAMAN NILAI-NILAI AGAMA DAN MORAL ANAK USIA DINI - Novia Safitri; Cahniyo Wijaya Kuswanto; Yosep Aspat Alamsyah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
The cultivation of moral and religious values in early childhood is very important so that students can have good moral and religious values, so that when students enter the next level, they already have knowledge, good experiences that have been obtained when they at the time pre school. This study discusses the cultivation of religious and moral values of early childhood in Goemerlang Sukarame Kindergarten, Bandar Lampung. The purpose of this study was to determine the cultivation of moral and religious values in early childhood in Goemerlang Sukarame Kindergarten, Bandar Lampung. This research is a descriptive qualitative study, which involves a teacher in class B2. Data were analyzed qualitatively using data reduction, data display, and conclusion drawing. The results showed that the activities of planting moral and religious values in Goemerlang Bandar Lampung Kindergarten had been well planned and implemented. There are several methods developed at Goemerlang Bandar Lampung Kindergarten for inculcating moral and religious values, namely the story telling method, the field trip method, the demonstration method, the assignment method, the habituation method, and the conversation method.